Tribological behavior of Fe3O4/MoS2 nanocomposites additives in aqueous and oil phase media. (October 2016) - Zheng, Xiaojing; Xu, Yufu; Geng, Jian; Peng, Yubin; Olson, Dustin; Hu, Xianguo
Abstract: To improve the dispersing effects of nanoparticles, Fe3 O4 /MoS2 nanocomposites were fabricated by precipitation of Fe3 O4 nanoparticles onto MoS2 nanosheets, and their tribological properties were investigated. The experimental results show that with an increase in the concentration of MoS2 nanosheets and Fe3 O4 /MoS2 nanocomposites in both aqueous and bio-diesel media, the friction coefficient and wear scar diameters (WSD) of the steel balls decreased significantly. The maximum decrease amounted to 34.6% for friction coefficient and 29.7% for WSD. The excellent lubricating mechanisms are ascribed to the well dispersed Fe3 O4 nanoparticles on MoS2 nanosheets; the combined effect of the nanoball bearing role of Fe3 O4 nanoparticles, slippery role of MoS2 nanosheets, adsorbed- and tribo-film help to reduce the friction and wear of the tribo-pairs. Highlights: Fe3 O4 /MoS2 nanocomposites have been synthesized and characterized. Tribological behaviors of the nanocomposites were investigated. Fe3 O4 /MoS2 nanocomposites display excellent tribological properties. The mechanism was discussed to explain their tribological performances.